New to Ehretiaceae: Keraunea. Re-evaluation of a genus of climbers from Brazil - Cheek, Martin; Lombardi, Julio A. [UNESP]; Simões, Ana Rita G.; Zuntini, Alexandre R. (Cold Spring Harbor Laboratory, 2023)
Abstract We definitively place Keraunea , a genus of showy forest climbers from remnants of the Mata Atlântica of Brazil, in Ehretiaceae. Previously Keraunea had been ascribed to Convolvulaceae based on morphology, or divided between Malpighiaceae and Ehretiaceae based on molecular analyses (polyphyletic). Keraunea is morphologically anomalous in the Ehretiaceae, having fruits which are held in the centre of a large wing-like bract by adnation of the pedicel, and due the stem-twining habit of some species. However, morphologically Keraunea shares two apomorphies with monotypic Cortesia Cav., halophytic shrubs of Argentina: 1) “two parted endocarps” (the fruit contains two endocarps each with two 1-seeded cells, while four 1-seeded endocarps are plesiomorphic in Ehretiaceae) and 2) a large bract that subtends the flower (absence of bracts is plesiomorphic in Ehretiaceae). A combined tree using four markers (ITS, trn L-F, rbc L and mat K) places the three species of Keraunea sampled unambiguously in a clade with Ehretia + Cortesia + Halgania and monophyly for Keraunea is shown with high support. In an ITS tree Keraunea is sister to Cortesia with low support. We expand the generic description of Keraunea including the first account of the internal fruit structures and the seed, and present new data on the vegetative architecture including variation within the genus, some species being stem twiners while one species at least, is described as a scandent shrub. Keraunea lombardiana , previously included within K. brasiliensis , is formally described from Minas Gerais and Bahia as the third species of the genus and both these species are described. In all five species are recognised but two, known to us only from digital images, are not formally described because sufficiently detailed descriptions cannot be made. All five species are mapped, and provisional conservation assessments are recorded, of either Endangered or Critically Endangered. The state of Bahia, with three species, has the highest species diversity, mainly in dry forest. Three species appear confined to moist coastal forest, extending southwards from Bahia to the state of Rio de Janeiro. Keraunea remains incompletely known. Not one of the species has both anthetic flowers and fruits described. Studies on pollen, germination, anatomy, embryology and phytochemisty are entirely lacking. Field observations of pollination, seed dispersal and phenology are also required. However, the most urgent requirement is undoubtedly a formal taxonomic revision based on a full herbarium search and targeted fieldwork, with full IUCN 2012 extinction risk assessments for each taxon. This is urgent because it seems that all the taxa that we present in this paper (and more that can be expected to be found) appear to be highly range restricted and generally not to occur in protected areas, and so appear to be highly threatened.